Multiple Sources of Cholinergic Input to the Superior Olivary Complex - Beebe, Nichole L.; Zhang, Chao; Burger, R. Michael; Schofield, Brett R. (Frontiers in Neural Circuits, 2021)
The superior olivary complex (SOC) is a major computation center in the brainstem auditory system. Despite previous reports of high expression levels of cholinergic receptors in the SOC, few studies have addressed the functional role of acetylcholine in the region. The source of the cholinergic innervation is unknown for all but one of the nuclei of the SOC, limiting our understanding of cholinergic modulation. The medial nucleus of the trapezoid body, a key inhibitory link in monaural and binaural circuits, receives cholinergic input from other SOC nuclei and also from the pontomesencephalic tegmentum (Zhang et al., 2021 J. Neurosci. 41:674-688). Here, we investigate whether these same regions are sources of cholinergic input to other SOC nuclei. We also investigate whether individual cholinergic cells can send collateral projections bilaterally (i.e., into both SOCs), as has been shown at other levels of the subcortical auditory system. We injected retrograde tract tracers into the SOC in gerbils, then identified retrogradely-labeled cells that were also immunolabeled for choline acetyltransferase, a marker for cholinergic cells. We found that both the SOC and the PMT send cholinergic projections into the SOC, and these projections appear to innervate all major SOC nuclei. We also observed a small cholinergic projection into the SOC from the lateral paragigantocellular nucleus of the reticular formation. These various sources likely serve different functions; e.g., the PMT has been associated with things such as arousal and sensory gating whereas the SOC may provide feedback more closely tuned to specific auditory stimuli. Further, individual cholinergic neurons in each of these regions can send branching projections into both SOCs. Such projections present an opportunity for cholinergic modulation to be coordinated across the auditory brainstem.